Stroke community awareness among public: a cross sectional study. - Anuar Deen MK,; Nik Azlan NM,; Mohd Fairuz A,; Zuraidah CM, (Penerbit UKM, 2014)
This study assessed the level of public awareness pertaining to risk factors, symptoms, treatment and source of information in relation to stroke and transient ischaemic attack. Stroke risk profile of the respondents was correlated with their level of knowledge. Using a validated pre-tested questionnaire, 112 respondents were recruited during two separate community events. Respondents completed the questionnaire and underwent health screening. The data were analysed using SPSS version 20. Overall knowledge was poor. Only 35% of the respondents had satisfactory knowledge of the warning signs (p= 0.94) and 29% had satisfactory knowledge on the risk factors (p=0.46). When analysed according to risk groups, 26%, 30% and 41% of respondents had satisfactory awareness in the low, intermediate and high risk group, respectively. None of the respondents knew about the availability of treatment of acute stroke in the emergency department or the importance of rehabilitation as part of stroke management. Public awareness on stroke risk factors, symptoms and management is poor.